COVID-19 second wave deadlier than first in pregnant women: a comparative observational study and the COVID saga continues - D, Suyajna Joshi; G., Vijayalakshmi; Rai, Rajeswari; Banu, Ruksar; ., Jayasakthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: A two wave pattern has been seen in many countries in reported cases of corona virus disease-19 during the 2020 pandemic. Observed data show that the effects of the virus do vary between the two periods. Differences in severity of the disease have been reported, although the comparative characteristics of the two waves still remain largely unknown. Methods: This was a prospective cross sectional study continuation of our first paper comparing 133 pregnant COVID-19 positive patients delivered at District Hospital, Bellary, in the first wave and 251 patients admitted during second wave. Results: In the present study 87.9% patients were in the age of 20-30 years, 90% patients belong to lower socio-economic status, mild anemia about 27.4% in second wave, moderate anemia seen in 16.7% in second wave, and 10.35% had severe anemia. Non-severe pre-eclampsia was present in 18.72% of the patients, severe pre-eclampsia was seen in 9.94% of the cases and 01.59% had gestational hypertension. Mode of delivery was 17.9% FTND, 3.77% FTVD emergency LSCS was 74.5% in second wave, and preterm delivery was seen in 3.77% in second wave. Elevated levels of D-dimer were found 34.6% in second wave. 14 deaths being reported in second wave. Conclusions: This study compared the obstetric and clinical outcome in COVID-19 positive patients who are in labor in first and second wave of COVID-19 infection. Although our conclusions are limited, the finding so obtained are important for understanding the clinical parameters, obstetric parameters and perinatal outcome in both waves with considerable increase in maternal mortality in second wave.